Suppression of Amyloid β A11 Antibody Immunoreactivity by Vitamin C: POSSIBLE ROLE OF HEPARAN SULFATE OLIGOSACCHARIDES DERIVED FROM GLYPICAN-1 BY ASCORBATE-INDUCED, NITRIC OXIDE (NO)-CATALYZED DEGRADATION - Cheng, Fang (American Society for Biochemistry and Molecular Biology, 2011)
Amyloid β (Aβ) is generated from the copper- and heparan sulfate (HS)-binding amyloid precursor protein (APP) by proteolytic processing. APP supports S-nitrosylation of the HS proteoglycan glypican-1 (Gpc-1). In the presence of ascorbate, there is NO-catalyzed release of anhydromannose (anMan)-containing oligosaccharides from Gpc-1-nitrosothiol. We investigated whether these oligosaccharides interact with Aβ during APP processing and plaque formation. anMan immunoreactivity was detected in amyloid plaques of Alzheimer (AD) and APP transgenic (Tg2576) mouse brains by immunofluorescence microscopy. APP/APP degradation products detected by antibodies to the C terminus of APP, but not Aβ oligomers detected by the anti-Aβ A11 antibody, colocalized with anMan immunoreactivity in Tg2576 fibroblasts. A 50–55-kDa anionic, sodium dodecyl sulfate-stable, anMan- and Aβ-immunoreactive species was obtained from Tg2576 fibroblasts using immunoprecipitation with anti-APP (C terminus). anMan-containing HS oligo- and disaccharide preparations modulated or suppressed A11 immunoreactivity and oligomerization of Aβ42 peptide in an in vitro assay. A11 immunoreactivity increased in Tg2576 fibroblasts when Gpc-1 autoprocessing was inhibited by 3-β[2(diethylamino)ethoxy]androst-5-en-17-one (U18666A) and decreased when Gpc-1 autoprocessing was stimulated by ascorbate. Neither overexpression of Gpc-1 in Tg2576 fibroblasts nor addition of copper ion and NO donor to hippocampal slices from 3xTg-AD mice affected A11 immunoreactivity levels. However, A11 immunoreactivity was greatly suppressed by the subsequent addition of ascorbate. We speculate that temporary interaction between the Aβ domain and small, anMan-containing oligosaccharides may preclude formation of toxic Aβ oligomers. A portion of the oligosaccharides are co-secreted with the Aβ peptides and deposited in plaques. These results support the notion that an inadequate supply of vitamin C could contribute to late onset AD in humans.